Strategies to relieve immunosuppression in pancreatic cancer. (April 2015) - Schnurr, Max; Duewell, Peter; Bauer, Christian; Rothenfusser, Simon; Lauber, Kirsten; Endres, Stefan; Kobold, Sebastian
Despite continuous progress in the understanding of deregulated pathways in pancreatic cancer cells and development of targeted therapies, therapeutic advances with clinical benefit have been scarce over the last decades. The recent success of immunotherapy for some solid cancers has fueled optimism that this approach might also work for pancreatic cancer. However, a highly immunosuppressive microenvironment mediated by tumor, stromal and immune cells creates a major hurdle for immunotherapy. Mouse models have helped to unravel critical immunosuppressive mechanisms that could serve as novel therapeutic targets. Here we review new promising strategies that alone or in combination with other modalities, such as chemotherapy or irradiation, have the potential to lead to tumor immune control and finally better clinical outcome.